2014
DOI: 10.1371/journal.pone.0092537
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Carriage of Staphylococcus aureus in Botucatu, Brazil: A Population-Based Survey

Abstract: Recent increases in the incidence and severity of staphylococcal infections renewed interest in studies that assess the burden of asymptomatic carriage of Staphylococcus aureus in the community setting. We conducted a population-based survey in the city of Botucatu, Brazil (122,000 inhabitants), in order to identify the prevalence of nasal carriage of Staphylococcus aureus (including methicillin-resistant strains). Nasal swabs were obtained from 686 persons over one year of age. Resistance to methicillin was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 67 publications
(73 reference statements)
6
30
1
1
Order By: Relevance
“…Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results have been reported in other studies [34,35]. A low frequency of the PVL gene was also observed in other studies conducted in the region [22,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with the findings of a population-based study conducted in Botucatu in 2011 aimed at identifying the prevalence of S. aureus in nasal carriers. The study demonstrated a prevalence of MRSA of 0.9%, all of them SCCmec type IV and PVL À and most isolates belonging to ST5 and ST1176 and spa type t002 [22]. ST1176 was described for the first time in S. aureus SCCmec IV in a study conducted at Hospital São Paulo in the city of São Paulo, Brazil, indicating the emergence of this new clone (ST-1776) as the causative agent of community-acquired and nosocomial infections in Brazil hla (2), hlb (2), hld (2), icaA (2), icaD (2) BHU14 (1); BHU3 (1) 2…”
Section: Discussionmentioning
confidence: 88%
“…According to the multivariate analysis, nasopharyngeal S. aureus carriage was associated with S. aureus SSTI, a finding similar to that in multiple previous studies on S. aureus carriage . Decolonisation may therefore be beneficial in such cases.…”
Section: Discussionsupporting
confidence: 86%
“…In that study, 32.7% and 0.9% of persons carried S. aureus and MRSA, respectively [9]. Even though these findings are somewhat puzzling, some remarks should be made regarding the study subjects.…”
Section: Discussionmentioning
confidence: 94%